The value relevance of brand valuation. Issue 58 (14th December 2017) - Bagna, Emanuel; Dicuonzo, Grazia; Perrone, Andrea; Dell'Atti, Vittorio
ABSTRACT: The reports published by independent parties are often used to provide an estimation of brands due to the lack of literature and best practices regarding which brand valuation method is more value relevant and reliable than another. Over the last several years, brand valuation debate is growing in importance because of the need to provide a value of intangibles for different purposes. The purpose of this study is two-fold. First, we aim to understand whether brand valuation related to listed companies provided by three independent agencies is value relevant and therefore whether these brand valuations are taken into consideration by investors in their decision-making process. Second, we assess which of the three methods reflects the stock markets in a better way. We analyse a sample of 71 brands valuated by Interbrand, Brand Finance and BrandZ from 2013 to 2015. The results show that brand valuation provided by the independent agencies is value relevant; in addition, they reveal that the Brand Finance method, based on the royalty relief approach, is more value relevant than the others. This study contributes to the extant literature on value relevance by providing evidence on the impact of stock prices of brand agencies' valuation.